Genetic Transformation and Mutagenesis via Single-Stranded DNA in the Unicellular, Diazotrophic Cyanobacteria of the Genus Cyanothece - Min, Hongtao (American Society for Microbiology (ASM), 2010)
We describe a genetic system for producing specific gene knockouts in Cyanothece sp. strain PCC 7822 using a single-stranded DNA technique (B. Zorin, P. Hegemann, and I. Sizova, Eukaryot. Cell 4:1264-1272, 2005). The first fully segregated mutant was a ΔnifK mutant, and it was unable to grow on medium lacking combined nitrogen and produced virtually no hydrogen.